New multiple cropping systems for higher production and profit - Sharma, S N; Prasad, R; Singh, S (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 1985-86 to 1987-88 at New Delhi, to compare the productivity and economics of 8 intensive annual cropping systems. Relay cropping of maize (Zea mays L.)-potato(Solanum tuberosum L.) + wheat (Triticum aestivum L. emend. Fiori & Paol.) gave the highest productivity (16.7 tonnes wheat equivalent/ha), gross income (Rs 41 726/ha), net income (Rs 18 145/ha) and labour employment (388 mandays/ha). Maize-potato-wheat sequential cropping, which gave the second-highest productivity (13.9 tonnes wheat equivalent/ha) and gross income (Rs 34 759/ha), was very poor in net return (Rs 11 495/ha), Greengram(Phaseolus radiatus L.)-maize-wheatcropping system proved the second best in net income, though the first 2 crops contributed only 9 and 17% of the total net income respectively, compared with 74% by the third crop. Pigeonpea [Cajanus cajan (L.) Millsp.] + greengram-wheat, being third-best cropping system, gave 50% net income from the first 2 crops and the rest 50% from the third. Thus pigeonpea did not prove a suitable replacement for maize. Though it gave more income (Rs 5 897-7 703/ha) than maize (Rs 1 433-2 838/ha), it delayed the wheat sowing and thus affected the productivity and net income of the cropping system.